OCB GURU DENGAN ANTECEDENT SPIRITUALITAS, KOMITMEN DAN ETIKA KERJA ISLAMI PADA GURU SD IT AL HUDA KEBUMEN - Azizah, Siti Nur (P4M STIE Putra Bangsa, 2015)
The purpose of this study is to determine the influence of Islamic Work Ethics, Organizational Commitment And Islamic Spiritulity against Organizational Citizenship Behavior (Case Study is Teachers In Islamic Elementary School Al Huda). The number of samples taken as many as 32 respondents with saturated sample method. Data collection using a Likert-scale closed questionnaire. The result of t test shows that the work ethic of Islam and islamic spirituality give positive and significant influence to OCB whereas organizational commitment has negative and significant effect to OCB with regression equation Y = 0,827 + 0,235X1 - 0,367X2 + 1,055X3. F test results show that the ethics of Islamic work, organizational commitment and job satisfaction have a positive and significant effect on OCB. While the value of coefficient determination is 0.892 which means that the work ethic of Islam (X1), organizational commitment (X2) and islamic spirituality (X3) have contribution to OCB (Y) of 89.2% while the rest 10.8% by another factor.